FUNGSI DAN MAKNA PENGGUNAAN KATA KERJA ~ていく ( ~ TE IKU) DAN ~てくる( ~TE KURU) PADA ANIME SKET DANCE - Rizka Septialis Septialis; Zuli Laili Isnaini Laili Isnaini; Nana Rahayu Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research describes about the function and meaning of the forms~ていくand ~てくる. The purpose of this research is to help students and other learners to understand the function and meaning of the forms ~ていくand ~てくるand they can use this forms in the correct situation.In Japanese grammatical[1]the form of ~teiku ( ~ていく) and~te kuru (~てくる)refers to connection between speaker potition on time or movement of the action.The form~teiku ( ~ていく) and~te kuru (~てくる)have a diffirent function,the form~teiku ( ~ていく) has several uses related to movement of the action of the place or time away from the speaker, and the form~te kuru (~てくる)which indicates movement in place or time towards the speaker.Tomomatsu said the function of the ~teiku ( ~ていく) and~te kuru (~てくる) there are eight function in different situation.Theory in this research is the function of the form~teiku ( ~ていく) and~te kuru (~てくる)theory by Tomomatsu. Descriptive method is the method that applied in this research. The writer used the data from Japanese anime with title Sket Dance.The result of this research is the function of the forms ~ていくand ~てくる in anime Sket Dance are function for explain the continuous situations, to explain that doing activity when go, movement activity, go and come back to the first place, movement draw to the speaker, to explain make the scene, and to explain the change of situation. There are ten function in different situation, and the situation can influence the function of the forms ~ていくand ~てくる. Keywords:Verb,~teiku , ~te kuru , movement of the action [1]Susunan kata-kata dalam frase, klausa, atau kalimat.